’DOL’ NET PRAWN FISHERY OF BOMBAY DURING 1966-76 - Rajan, K N; Sukumaran, K K; Pillai, S Krishna (Indian Journal of Fisheries, 2011)
The best prawn catches of 2330.4 t at Versova were in 70-71 and 1917.5 t at Sassoon Docks were in 1968-69. The peak fishery was generally during October- December and March-May. The fishery was supported mainly by seven species of penaeids and three species of non-penaeids; the latter contributing up to 80% of the catches obtained in Dol nets.